PKM Desa Doplang Kecamatan Bawen Kabupaten Semarang - Valdyan Drifanda; Rosalina Ginting; Antono Herry Purnomo Adhi (Pusat Riset dan Inovasi Nasional, 2024)
The Community Service activities that have been carried out aim to improve the welfare of the people of Doplang Village by optimizing all potential, both natural resources and human resources, to be integrated into the Edupark Agricultural Plantation Tourism Object. This term was chosen because the tourist village that will be created will not only rely on natural potential but also has educational value for tourists who visit this tourist village. There are 3 solutions offered by PGRI University Semarang in the framework of overcoming the problems faced by the Doplang village community, including training in making processed tuberose flowers into healthy preservative-free food, training in MSME financial management and training in Organizational Management, Tourism Management, Tourism Management SOPs , Layout (Master Plan) of Tourist Villages. The results of this program are providing theoretical provisions related to the cultivation of tuberose plants, providing theoretical and practical provisions related to food processing from tuberose plants, providing materials and workshops related to strategies for making tourism products along with tips for their development, and providing theoretical provisions related to Tourism Law.